Attitude of Asian Parkinson Patients towards Clinical Research and Tissue Donation. (19th February 2020) - Khan, Shazma; Foo, Joel Y. J.; Chia, Nicole S. Y.; Agustin, Sherwin J. U.; Neo, Shermyn X. M.; Tay, Kay-Yaw; Au, Wing-Lok; Ng, Adeline S. L.; Tan, Louis C. S.
Abstract : Objective . The success of clinical research and tissue donation programs are highly dependent on recruitment of willing volunteers. A comprehensive survey of patient preferences and attitudes can help identify and address barriers hindering the recruitment for research. Method . This is a cross-sectional study on 105 Parkinson's disease patients who completed an interviewer-administered questionnaire. Results . Out of 105 respondents, 48% of patients had either already participated in clinical research or were keen to participate. About 80% believed clinical research to be safe for their health and privacy. More than 70% of participants were willing to donate blood, urine, or stool, while 16% were agreeable for cerebrospinal fluid sample donation. Motivating factors for clinical research included altruism (64%) and contribution to advance medical knowledge (64%). Common reasons for unwillingness towards clinical research included the risks involved (43%), time constraints (33%), and mobility challenges (24%). Conclusion . The attitude of Singaporean Parkinson patients toward clinical research and tissue donation is encouraging with about half of the participants willing to support clinical research. Three-quarters of patients would support tissue donations. Participation in research may be further increased with greater patient and public education to overcome misconceptions and also by limiting the demands of studies.